4.26 STABILITY IN SOCIAL RELATIONSHIPS - Salimov Bakhriddin Lutfullaevich. Professor at Tashkent State Transport University. Valiyev SHoxuja Tirkash o‘g‘li. Student at Tashkent State Transport University. (Innovative technologies in construction Scientific Journal, 2023)
Аnnotation In the article, it is philosophical that no one can correctly say what will happen tomorrow, from which direction the danger will come, the world surrounding us today is becoming extremely complex and will remain so in the near future, therefore the issue of maintaining the path of sustainable development will always be relevant for the nations. analyzed in terms of Key words: world, country, risks, uncertainty, purpose, stability. What is liveliness? What is a sense of life? Questions about the purpose of human life have plagued humanity for thousands of years. The answers to such questions of representatives of humanity, considered the most perfect among beings, were explained in different contexts during different periods, but the relevance of these questions has not lost its significance today. After all, a person who is considered a conscious being, living in this world, seeks meaning in his life, gets confused in difficult situations that arise in his life, and tries to find a solution to them. Sometimes he finds answers to his questions, sometimes he struggles to find answers. In fact, it is difficult to find a 100% answer to questions of this nature. Just as the socio-economic, political-legal, cultural and educational conditions of societies that existed in different eras are different, so the way of life of people who have survived to this day and are living at the same time has never been the same and will never be the same. It follows from this that it is natural that each society, each person has different views on life and answers to questions arising in connection with this. However, it must be recognized that the situations in some societies and the lifestyles of some people may be partly similar. Then their conclusions about life will be compatible with each other. Then there will be opportunities to learn from the lifestyle of others, to avoid mistakes and shortcomings made by them. As we mentioned above, these aspects are also relevant to societies, states, in particular, to the fate of Uzbekistan. After all, “What will the 21st century be like for the people of Uzbekistan?” How much better will people's lives be than yesterday? Do we understand that the path of reform and renewal that we have chosen for ourselves is very difficult? Do we have a clear enough idea of what problems, difficulties and trials we may encounter along the way? these thoughts should never leave us. We think that then our future will be great. That is why, “at the same time, with a deep analysis of the development path of our country, today the situation on the world market has changed dramatically, and competition in the context of globalization is becoming more intense, which requires the development and implementation of a completely new approach and principles for the development of our country more stable and at a fast pace." The situation shows that not everyone can correctly understand what will happen tomorrow, from which side the danger will come. Today, “the world around us is becoming extremely complex and will remain so in the near future.” Resilience cannot be maintained simply by being aware of these risks, simply by assessing them. So what should be done?! As a correct answer to this question, the following points can be cited: “It seems that it is not enough to be able to relate to the threats to security and stability that arise today. We need to understand the nature of the dangers that exist. We need to determine their sources and interactions over time. We need to determine the conditions for maintaining stability in society and use them effectively. The stable and progressive development of the Republic of Uzbekistan depends on them.” In fact, maintaining peace and tranquility is very important for Uzbekistan, which has chosen its independent path of development and is now becoming more and more stable in the conditions of market relations, and all kinds of unexpected disasters and the instability caused by them pose an equally great danger. After all, society and the state, moving from one system to a completely new system, can be brought to the brink of destruction even by unexpected disproportions. Therefore, work in this area must be done with extreme caution. “The transition from a command-and-control style of centralized planning and management to a market economy is not an update or improvement of the existing way of doing business, but the introduction of an entirely new system of doing business. This is a transition from one state of quality to another. This is a completely new philosophy of life for people. Accordingly, it cannot be implemented as a one-time event, but requires a long period, including several stages. Now, along with material needs, people also have spiritual needs, without which it is difficult to imagine our lives today. In particular, one of these needs is the desire of a person to know his identity. In fact, every person with a certain level of intelligence and understanding should strive to know who he is, choose his own path in life, and, if necessary, try to build for himself a “Free and prosperous homeland, a free and prosperous life.” Every compatriot living in independent Uzbekistan, if we think about these things, if we think about them, then not only these, but also other issues, problems and goals should always be the focus of our attention. The introduction of the said philosophy of life into the consciousness of our people should be, first of all, one of the main tasks of the social and human sciences, in particular such sciences as philosophy, sociology, the national idea, and the foundations of spirituality. REFERENCES Salimov B.L. Expression of Dialectic Categories in the Individual’s Social Life // eu. International Journal of InnovativeAnalyses and Emerging Technology. Volume: 1, lssue 4, 2021. -Р.16-18. Salimov Baxriddin Lutfullaevich. The philosophical role of dialectical categories in human life. Oriental Renaissance: Innovative, educational, natural and social sciences. Volume: 1, lssue 6, 2021. -Р.406-410. Salimov Baxriddin Lutfullaevich. Prospects of Development of Communication and Transport System in Uzbekistan. WEB OF SYNERGY: International Interdisciplinary Research Journal. Volume 2 Issue 2, Year 2023 ISSN: 2835-3013. Salimov, B., Madalimov, T. (2023). Transport falsafasi. Globe Edit. Salimov Bakhriddin Lutfullaevich. The Importance of Sea Transport in the Communication System. WEB OF SYNERGY: International Interdisciplinary Research Journal. Volume 2 Issue 1, Year 2023 ISSN: 2835-3013. Salimov Bakhriddin Lutfullaevich. The Influence of the Transport and Communication System on Social Relations. Web of Semantic: Universal Journal on Ie Education. Volume 2 Issue 2, Year 2023. ISSN: 2835-3048. Salimov Bakhriddin Lutfullaevich. Reforms in the Fields of Communication and Transport and their Social Impact. Web of Semantic: Universal Journal on Ie Education. Volume 2 Issue 2, Year 2023. ISSN: 2835-3048. Салимов Б.Л. Ижтимоий муносабатларнинг коммуникация ва транспорт тизими билан детерминистик боғлиқлигининг гносеологик таҳлили. Фалсафа фанлари доктори диссертацияси. Ўзбекистон Миллий университети. Тошкент. 2022, 224 б. Salimov Bakhriddin Lutfullaevich, Tursunov, Shokhijakhan Ravshanovich, Haydarov, Mehriddin Nuriddin Ugli (2023). SYNERGETIC APPROACH IN THE ANALYSIS OF SOCIAL RELATIONS. Oriental renaissance: Innovative, educational, natural and social sciences, 3 (3), 1001-1007. Bakhriddin Lutfullaevich Salimov. NEGATIVE CONSEQUENCES OF SCIENCE AND TECHNOLOGY DEVELOPMENT. International Conference" Law, Economics and Tourism sciences in the modern world". 2023/5/1. С. 5-10.